Digital detox : the politics of disconnecting - Syvertsen, Trine (SocietyNow., 2020)
Against a backdrop of increasingly intrusive technologies, Trine Syvertsen explores the digital detox phenomenon and the politics of disconnection from invasive media. With a wealth of examples, the book demonstrates how self-regulation online is practiced and delves into how it has also become an expression of resistance in the 21st century.